Morpho-physiological responses of wheat (Triticum aestivum L.) and rice (Oryza sativa L.) to chromium stress: Chromium stress in wheat and rice - Sarangi, Ansul; Das, Manoja; Behera, Kambaska Kumar; Samal, Nibedita (ORYZA-An International Journal of Rice, 2025)
Hexavalent chromium (Cr+6) contamination poses a severe threat to crop productivity by impairing plant physiological and biochemical functions. This study investigated the impact of increasing Cr concentrations (20-80 mg l-1) on shoot and root growth, biomass accumulation, pigment content, and antioxidant responses in hydroponically grown wheat (Triticum aestivum L. cv. HD-2894) and rice (Oryza sativa L.cv. Sabita) seedlings, along with the mitigating roles of chelating agents, diethylenetriaminepentaacetic acid (DTPA) and ethylenediaminetetraacetic acid (EDTA). Chromium stress significantly reduced shoot and root length (up to ~40%), biomass (up to ~61%), and photosynthetic pigments (chlorophylls and carotenoids by ~35-59%) in both crops. Protein content declined by ~15%, while proline increased up to 10.4-fold in wheat and 8.7-fold in rice, indicating strong oxidative stress. Chelator application reversed these effects: DTPA at 20 mg L-1 Cr enhanced wheat shoot biomass by 1.20-fold and rice shoot length by 1.18-fold over control, while EDTA provided comparable improvements. Antioxidant enzyme activities (peroxidase, catalase, superoxide dismutase) increased significantly under Cr exposure, with maximum SOD activity reaching 36.25 unit g-1 of the fresh weight in rice root (8.06-fold over control) under EDTA. DTPA and EDTA improved antioxidant defense, nutrient uptake, and growth recovery, with DTPA slightly more effective for growth restoration and EDTA for enzymatic stimulation. These findings highlight the protective roles of DTPA and EDTA in mitigating Cr+6-induced stress and suggest their potential use in enhancing metal tolerance and phytoremediation efficiency in wheat and rice.